Microbial diversity as an indicator of a diversified cropping system for luvisoils in a moderate climate. Case study – Long term experiments from Poland. (August 2022) - Górska, E.B.; Stępien, W.; Cunha, A.; Sierra-Garcia, I.N.; Szyszkowska, K.; Gozdowski, D.; Gworek, B.; Sas-Paszt, L.; Lisek, A.; Hewelke, E.; Prędecka, A.; Olejniczak, I.; et al.
Graphical abstract: Highlights: The method of tillage effect on microbial diversity and metabolism genes. The lack of plow cultivation resulted in Nitrospirae dominating the soil. The abundance of Sorangium sp. in the soil is independent of plow cultivation. Mycobacterium sp. can may be an indicator of resistance to no-till in soil. Gemmatimonas sp. can be recommended as indicator to prolonged lack of plowing. Abstract: The idea of agricultural sustainable in the EU is based on, both minimizing interference with the soil system as well as diversifying crop rotation what relates to the limited cultivation system (changed from plow to no-plowing tillage) as well as organic fertilization is often abandoned. Taking above into account, our goal was determined of the structure, composition, and metabolic profiles of soil microbiomes in various cultivation methods (under multiannual plow and no-plow cultivation) using metagenomic analysis. Having regard to the recommendations contained in EU report (European Commission et al., 2020 ) of the Mission board for Soil health and food, 2020 indicating the lack of microbiological indicators of "healthy soil". So, we have tried to select of microbiological indicators showing sensitivity and resistance to use the methods of soil cultivation. The research object was located on almost 100-year field experiments at the Experimental Station of the Faculty of Agriculture and Biology in Skierniewice/near Warsaw on, luvisoils dominated in the temperate climate of Central Europe. Soil microorganisms respond with changes in their abundance and taxonomic composition depending on the methods of soil cultivation. Actinobacteria were the most abundant, while Planctomycetes were the least abundant in the metagenome of soil fertilized with manure, whereas the uncultivated soil was dominated by Nitrospirae . We can recommend the following taxa, including Gemmatimonas sp. as a microbiological indicator sensitive to the long-term lack of both plow cultivation of soil and organic fertilization, and Mycobacterium sp. as a resistancivity indicator to this soil cultivation method. Sorangium sp. could be recommended as microbiological indicators which responds by reducing the quantity under effect of the organically fertilized soil, while the plow and no-plow cultivation does not affect changes in its quantity. The use of various cultivation methods changed the biochemical functions in soil metagenoms, including nitrogen and sulfur metabolism and carbohydrate metabolism, and in the production of plant hormones and siderophores. Additionally, soil cultivation ways changed the response of microorganism's stresses, including oxidative stress. The conducted research indicates the necessity to conduct further research on the influence of various cultivation methods, on the diversity of the microorganism community and soil metabolism. The result of which may be the selection of appropriate microbiological indicators for determining "soil health" depending on the type of soil under cultivation located in different climatic zones, not only presented in the paper.